2014
DOI: 10.12816/0023976
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein ( a ) and Atherogenic Indices in Sudanese Patients with Type 2 Diabetes

Abstract: Background & Aims: Type 2 diabetes is associated with significant cardiac morbidity and mortality with a more than threefold increased risk of coronary artery disease (CAD). We aimed to assess the serum concentrations of lipoprotein (a) and lipid profile indexes as predictors for CAD in Sudanese type 2 diabetics compared to healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(17 reference statements)
2
1
0
Order By: Relevance
“…Studies on Lp(a) levels in Africa have also reported elevated levels in the T2DM population. Mohieldein et al in 2014 reported that T2DM patients in Sudan had a significantly higher Lp(a) level [22]. This was similar to the finding of Ogbera and Azenabor in Nigeria [23].…”
Section: Discussionsupporting
confidence: 63%
“…Studies on Lp(a) levels in Africa have also reported elevated levels in the T2DM population. Mohieldein et al in 2014 reported that T2DM patients in Sudan had a significantly higher Lp(a) level [22]. This was similar to the finding of Ogbera and Azenabor in Nigeria [23].…”
Section: Discussionsupporting
confidence: 63%
“…This prevalence of hyperlipoproteinemia (a) in type 2 diabetics varies from one study to another and from one country to another. A Moroccan study by Idrissi et al [12] showed a prevalence of around 31.2% which is almost identical to ours while a Sudanese study by Mohieldein et al [13] presented a prevalence of 51.4% which is significantly higher than our results. These differences observed in the prevalence of hyperlipoproteinemia (a) within these different studies could be linked to the ethnic and racial variability of the populations studied, to the different dosing methods used but also and above all to the usual values taken into consideration as a threshold value for the risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings were confirmed by several other studies [14,15]. However, the Sudanese study by Mohieldein et al [13] showed results which contradict ours where the mean serum Lp(a) values were significantly higher in their healthy controls compared to their type 2 diabetic patients. Plasma Lp(a) concentrations are generally established by age 5 and remain constant throughout adulthood [11] but the pathophysiological mechanism by which individuals with type 2 diabetes have higher plasma levels has not been well elucidated, Hernández et al [16] believe that triglycerides and urinary albumin excretion rate are the main factors influencing serum Lp(a) levels in the diabetic population.…”
Section: Discussionsupporting
confidence: 85%
“…In the atherothrombotic range [8], Lp(a) levels of ≥ 75 nmol.L −1 were defined as abnormally high [24], and used to define CVD risk [12]. The prevalence of Lp(a) > 75 nmol.L −1 in our study was 31.2%, this result are in accordance with previus findings [24][25][26][27]. Heller FR, et al [25] found a prevalence about 20% in 146 patients with Diabetes Mellitus.…”
Section: Laboratory Examinationsupporting
confidence: 93%